Tomato chlorosis virus CPm protein is a pathogenicity determinant and suppresses host local RNA silencing induced by single-stranded RNA - Yang, Xiao; Luo, Xiangwen; Zhang, Yu; Zhang, Zhanhong; OuYang, Xian; Shi, Xiaobin; Lv, Xiaoyuan; Li, Fan; Zhang, Songbai; Liu, Yong; Zhang, Deyong (Frontiers in Microbiology, 2023)
Tomato chlorosis virus (ToCV) is a typical member of the genus Crinivirus, which severely threatens Solanaceae crops worldwide. The CPm protein encoded by ToCV has been reported to be associated with virus transmission by vectors and is involved in RNA silencing suppression, while the mechanisms remain ambiguous. Here, ToCV CPm was ectopically expressed by a potato virus X (PVX) vector and infiltrated into Nicotiana benthamiana wild-type and GFP-transgenic16c plants. The phylogenetic analysis showed that the CPm proteins encoded by criniviruses were distinctly divergent in amino acid sequences and predicted conserved domains, and the ToCV CPm protein possesses a conserved domain homologous to the TIGR02569 family protein, which does not occur in other criniviruses. Ectopic expression of ToCV CPm using a PVX vector resulted in severe mosaic symptoms followed by a hypersensitive-like response in N. benthamiana. Furthermore, agroinfiltration assays in N. benthamiana wilt type or GFP-transgenic 16c indicated that ToCV CPm protein effectively suppressed local RNA silencing induced by single-stranded but not double-stranded RNA, which probably resulted from the activity of binding double-stranded but not single-stranded RNA by ToCV CPm protein. Taken together, the results of this study suggest that the ToCV CPm protein possesses the dual activities of pathogenicity and RNA silencing, which might inhibit host posttranscriptional gene silencing (PTGS)-mediated resistance and is pivotal in the primary infection of ToCV-infected hosts.